Performance characterization of a 3D liquid scintillation detector for discrete spot scanning proton beam systems. (23rd June 2017) - Darne, Chinmay D; Alsanea, Fahed; Robertson, Daniel G; Sahoo, Narayan; Beddar, Sam
Abstract: Existing systems for proton beam dosimetry are limited in their ability to provide a complete, accurate, and detailed account of volumetric dose distribution. In this work, we describe the design and development of a portable, fast, and reusable liquid scintillator-based three-dimensional (3D) optical detection system for use in proton therapy. Our long-term goal is to use this system clinically for beam characterization, dosimetry, and quality assurance studies of discrete spot scanning proton beam systems. The system used a 20 × 20 × 20 cm 3 liquid scintillator volume. Three mutually orthogonal cameras surrounding this volume captured scintillation photons emitted in response to the proton beams. The cameras exhibited a mean spatial resolution of 0.21 mm over the complete detection volume and a temporal resolution of 11 ms. The system is shown to be capable of capturing all 94 beam energies delivered by a synchrotron and performing rapid beam range measurements with a mean accuracy of 0.073 ± 0.030 mm over all energies. The range measurement uncertainty for doses less than 1 cGy was found to be ±0.355 mm, indicating high precision for low dose detection. Finally, we demonstrated that using multiple cameras allowed for the precise locations of the delivered beams to be tracked in 3D. We conclude that this detector is capable of real-time and accurate tracking of dynamic spot beam deliveries in 3D. The high-resolution light profiles it generates will be useful for future 3D construction of dose maps.